Suspected Tuberculous Pleurisy and Coronavirus Disease 2019 Comorbidity - Yamaguchi, Yoh; Hashimoto, Masao; Saito, Susumu; Morita, Tie; Tsukada, Akinari; Kusaba, Yusaku; Katsuno, Takashi; Suzuki, Manabu; Takasaki, Jin; Izumi, Shinyu; Matsunaga, Akihiro; Ishizaka, Yukihito; et al. (Internal Medicine, 2022)
A 33-year-old woman with a fever, cough, and pharyngitis was admitted after left-sided pleural effusion was detected. The fever and upper respiratory symptoms were confirmed, and she was diagnosed with coronavirus disease (COVID-19) after showing a positive polymerase chain reaction (PCR) test. After thoracentesis, pleural fluid revealed elevated adenosine deaminase values and a positive QuantiFeron test; tuberculous pleurisy was thus suspected. Subsequent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) PCR and anti-SARS-CoV-2 Spike IgG tests were negative, suggesting that the initial PCR result had been erroneous. However, we were unable to confirm this. Data concerning COVID-19 diagnostics are insufficient at present. It is important to make comprehensive judgments regarding the diagnosis and treatment of patients as well as public health.